黄展鸣《天界无限》的女英雄形象 = Heroine images in Wee Tian Beng’s celestial zone - 谢文良 Chia, Boon Liang (2010)
奇幻武侠漫画世界一直是一个以男性为主要英雄的世界，但新加坡漫画家黄展鸣却大胆地创作以女英雄为主线的漫画，《天界无限》，并且在新加坡大受好评，续集不断，甚至还推广至亚洲、欧美及澳洲等地。本文将以女性主义的角度分析《天界无限》这个文本里的女英雄。In the world of chivalry comics, it had always been a land of male heroes. But Singapore comic artist Wee Tian Beng boldly created a set of comics titled Celestial Zone with heroines as his main focus. Celestial Zone received great response and feedback in Singapore, thus it develops into more series and it was even translated in a few other languages and promoted to Asia, Europe, America and Australia. This thesis will be analyzing the heroines in Celestial zone from the point of view of feminism. Firstly, I will be analyzing the heroine’s background, personality, realization, and how all these deconstruct the male-dominant ideology. Next, I will analyze the signs and symbols surrounding the heroines, like the hair and sword. Lastly, I will compare the heroines from Celestial zone with some existing heroine images like Mulan, Mu Gui Ying, Fan Li Hua, Huang Rong etc, and point out how the heroines from Celestial zone improved from the feminism point of view.